Activity-dependent peptidergic modulation of the plateau-generating neuron B64 in the feeding network of Aplysia - Koh, Hae-Young; Weiss, Klaudiusz R. (AMER PHYSIOLOGICAL SOC, 2007)
Many behaviors display various forms of activity-dependent plasticity. An example of such plasticity is the progressive shortening of the duration of protraction phase of feeding responses of Aplysia that occurs when feeding responses are repeatedly elicited. A similar protraction-duration shortening is observed in isolated ganglia of Aplysia when feeding-like motor programs are elicited through a prolonged stimulation of the command-like neuron CBI-2. Here, we investigate a cellular mechanism that may underlie this activity-dependent shortening of protraction duration of feeding motor programs. CBI-2 contains two neuropeptides, CP2 and FCAP. Previous work showed that CP2 shortens protraction duration of CBI-2 elicited programs. We show here that the same is true for FCAP. We also show that both CP2 and FCAP modulated the biophysical properties of a plateau-generating neuron, B64, that plays an important role in terminating the protraction phase of feeding motor programs. We find that prestimulation of CBI-2, as well as superfusion of CP2 and FCAP, lowered the threshold for activation of the plateau potential in B64. The threshold-lowering actions of CBI-2 prestimulation were occluded by superfusion of FCAP and CP2. Furthermore, at elevated temperature, conditions under which peptide release is prevented in Aplysia, prestimulation of CBI-2 does not lower the plateaupotential-threshold, whereas superfusion of CP2 and FCAP does. Our findings are consistent with the hypothesis that peptides released from CBI-2 lower the threshold for activation of plateau potential in B64, thereby contributing to the shortening of protraction duration when CBI-2 is repeatedly activated.
Keywords: COMMAND-LIKE NEURON; POSTTETANIC POTENTIATION; MOTOR PROGRAMS; COTRANSMITTERS; INTERNEURONS; MECHANISMS; BEHAVIOR; CIRCUIT; RELEASE; ELEMENT